Permasalahan Sampah Dan System Pengelolaan Sampah Pasar Tanjung Jember - Akbil Mastufatul; Safira Nuris; Niken Pupitasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Waste problems that have not been resolved so far have also been experienced in the Tanjung Market area, Jember Regency. The waste problems at Tanjung Market are an ineffective management system, the accumulation of waste that is not sorted into one, and the absence of a special party assigned by the market manager to handle and control hygiene problems and waste in the market which causes a lot of waste to be scattered around the market. everywhere. Not only from the traders side but this is also caused by the visitors or buyers at the market, most of them do not have the sensitivity and awareness to be able to dispose of waste in its place. So we need an environmentally sound waste management system with 3R techniques such as converting waste into useful materials efficiently and economically with minimal environmental impact.